Vegetative Bacillus amyloliquefaciens cells do not confer protection against necrotic enteritis in broilers despite high antibacterial activity of its supernatant against Clostridium perfringens in vitro. Issue 3 (3rd May 2016) - Geeraerts, S.; Delezie, E.; Ducatelle, R.; Haesebrouck, F.; Devreese, B.; Van Immerseel, F.
Abstract: In this study, the effect of Bacillus amyloliquefaciens on Clostridium perfringens was tested in vitro and in vivo . Using an agar well diffusion assay, the inhibitory activity of B. amyloliquefaciens supernatant was analysed against a large collection of netB-positive and netB-negative C. perfringens strains. Although strong growth inhibiting activity was detected against all C. perfringens isolates, it was significantly higher against virulent netB-positive C. perfringens strains compared with avirulent netB-negative isolates. Subsequently, the efficacy of in-feed administration of lyophilised vegetative cells of B. amyloliquefaciens to prevent necrotic enteritis was tested in vivo using an established experimental infection model in broilers. Ross 308 broilers received either B. amyloliquefaciens supplemented or unsupplemented feed throughout the experiment. No significant differences could be detected between the untreated positive control group and the B. amyloliquefaciens treated group in body weight, the number of chickens that developed necrotic lesions and in pathological lesion scores. These results demonstrate that despite its substantial inhibitory activity in vitro, lyophilised vegetative B. amyloliquefaciens cells had no beneficial effect against necrotic enteritis in the in vivo model used here.